Unsafe River Bank Houses? A Legal Reflection on Issues of Freedom from Poverty, Development Programmes and Accountability Mechanisms in Indonesia - Erna Dyah Kusumawati (Jember University Press, 2018)
Millions of the most deprived people worldwide live in slums with a lack of access to adequate water, hygiene and sanitation. Inadequate housing and living conditions increase vulnerability to other problems. For example, people living on the river banks in Jakarta regularly experience flooding due to adverse environmental conditions. Not only do the river bank settlements suffer from floods, but also other settlements as well as offices in Jakarta encounter similar effects. These regular floods cause billions of Indonesian Rupiah’s (IDR) in damages annually. As part of flood prevention programmes, the Jakarta government has evacuated and emptied the river bank settlements and has relocated the residents to rented, public high-rise housing provided by the municipality. This article will not address the legal issues of the relocation. Rather, it will examine whether relocation and resettlement due to development programmes can be addressed from a different perspective focusing on human rights as a means to eliminate poverty. It will also investigate the available accountability mechanisms at both the international and national level. Furthermore, it will assess whether these mechanisms can be employed to address the effect of development programmes which disproportionally affect people living on river banks. This study will use the classic legal research method, i.e. the normative legal method, to answer the research questions. In addition, it will also employ the human rights-based approach in assessing the regulation and policies adopted by the Indonesian authorities. The final part of this article will provide conclusions and recommendations for policymakers to address the societal problems by employing the human rights approach in tackling poverty and reducing the negative impacts of developments.